Illegible infrastructures: Road building and the making of state-spaces in the Colombian Amazon (2019)
The Amazon is currently experiencing a rapid growth in the building of transport infrastructures. While national governments have portrayed infrastructure development as greatly enhancing economic and geographical integration, critical approaches largely describe such development as a destructive process of resource extraction and dispossession. While these views differ radically in relation to the ends and effects of current and future infrastructure projects, they both conceive infrastructure as reflective of an inexorable process of state and capitalist expansion region-wide. Less attention has been paid, however, to the ways in which this very process is conditioned, and sometimes hindered, by a wide array of normative, social and political (dis) orders. In this paper, I draw attention to the ever conflicting and contingent nature of infrastructure building through an ethnographic account of the land conflicts present in an ongoing road project in the Colombian region of Putumayo. Specifically, I look at the tensions and disputes arising from the project’s attempts to make a target space and population legible in order to make them governable. By showing how such attempts have consistently failed and led the project into various states of suspension and uncertainty, the paper sheds light on the deep embedding of infrastructure in everyday dynamics of state-making and unmaking. © The Author(s) 2018.